Nationalencyklopedins ordbok - några karakteristiska typer av information - Malmgren, Sven-Göran (Nordiske Studier i Leksikografi, 1995)
In this paper, some characteristics of a new defining dictionary of Swedish, Nationalencyklopedins ordbok (NEO; The dictionary of the National Encyclopedia), are presented. The three-volume dictonary, comprising about 62 000 lemmas, will appear in 1995-96. Partly, it is based on another dictionary of Swedish, Svensk ordbok (SOB; A dictionary of Swedish). However, there are several new -or partly new -informational categories in the NEO, accounted for in the paper. These categories are (1) etymologies (for about half of the lemmas) and years of the first known occurrence (for every lemma and every numbered sense ); (2) valency; (3) morphological analysis; ( 4) word formation; (5) musical accent, and (6) references to synonyms, antonyms, co-hyponyms, etc.